Coping Style, Insomnia, and Psychological Distress Among Persons With Gastrointestinal Cancer. Issue 6 (6th November 2022) - Lv, Gaorong; Zhao, Di; Li, Guopeng; Wang, Qing; Zhou, Miao; Gao, Yiming; Zhao, Xiangyu; Li, Ping
Abstract : Background: Although insomnia has been shown to play an important role in psychological distress among gastrointestinal cancer patients, little is known about the internal mechanisms underlying this relation. Coping styles have been shown to moderate the effect of sleep on emotion, and this moderating effect may be age-dependent. Objective: The aim of this study was to test how age and coping styles moderate the role of insomnia on psychological distress among gastrointestinal cancer patients. Methods: This was a descriptive cross-sectional study with a convenience sample. A total of 352 patients with gastrointestinal cancer from two tertiary hospitals were recruited to participate in this study. The Kessler Psychological Distress Scale, the Insomnia Severity Index, and the Simplified Coping Style Questionnaire were used to assess patients' psychological distress, insomnia, and coping styles, respectively. We performed hierarchical multiple regression and Johnson–Neyman statistical analysis to probe the moderating effect of coping styles and age. Results: The mean age of the participants was 58.32 years. Nearly half of the participants reported psychological distress, and many reported insomnia. Insomnia was significantly positively associated with psychological distress. Coping styles and age moderated the relationship between insomnia and distress. Specifically, positive coping buffered the effect of insomnia on psychological distress only for subjects aged 34 years and younger; negative coping exacerbated the above relationship in patients aged 68 years and older while weakening the relationship in participants aged 51 years and younger. Discussion: There are age differences in the moderating role of coping styles on the relationship between insomnia and distress among gastrointestinal cancer patients. This study provides preliminary evidence to inform tailored guidance on coping styles by age groups to attenuate the risk for psychological distress related to insomnia in the cancer population.